2019
DOI: 10.3390/molecules24010197
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Five Iridoid Glycosides from Lonicerae Japonicae Flos Using High-Speed Counter-Current Chromatography and Their Anti-Inflammatory and Antibacterial Activities

Abstract: A high-speed counter-current chromatography (HSCCC) method, using a two-phase solvent system composed of ethyl acetate/n-butanol/methanol/water (5:1:1:5, v/v/v/v), was successfully established to separate the five iridoid glucosides 7-O-ethyl sweroside (1), secologanin dimethylacetal (2), adinoside F (3), (7R)-secologain n-butyl methyl acetal (4) and adinoside G (5) from Lonicerae Japonicae Flos. Their purities were 96.8%, 98.5%, 93.3%, 98.0% and 99.9%, respectively. All the iridoid glucosides were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In several regions of China, the former three are commonly used as foods. Several studies indicated that these four plants have anti-obesity or liver protection properties (6)(7)(8)(9)(10)12,13). Thus, we proposed that YZH may be a promising strategy for NAFLD management.…”
Section: Original Articlementioning
confidence: 94%
“…In several regions of China, the former three are commonly used as foods. Several studies indicated that these four plants have anti-obesity or liver protection properties (6)(7)(8)(9)(10)12,13). Thus, we proposed that YZH may be a promising strategy for NAFLD management.…”
Section: Original Articlementioning
confidence: 94%
“…Moreover, iridoid glycosides are responsible for antibacterial 12 , anti-allergic 13 , hepatoprotective 14 , and other pharmacological properties. Iridoid possess neuroprotective 15 , anti-thrombotic, and anti-inflammatory effects 16 . The accumulation and synthesis of bioactive constituents mainly depend on satisfactory growing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some species of this genus can also be used in functional foods, cosmetics and other applications, such as Lonicerae japonica Thunb. [ 7 ]. L. japonica Thunb., as a kind of traditional Chinese medicine for both medicine and food, can be used to make herbal tea and toothpaste and so on.…”
Section: Introductionmentioning
confidence: 99%